PENGARUH SUPERVISI KEPALA SEKOLAH DAN REWARD TERHADAP KINERJA GURU SD NEGERI DI KECAMATAN BANGKO KABUPATEN ROKAN HILIR - Aslina, Aslina; Azhar, Azhar; Gimin, Gimin (STKIP Pesisir Selatan, 2022)
This study aims to analyze the contribution of two independent variables, namely principal supervision and reward, and one dependent variable, namely teacher performance at SD Negeri Bangko District, Rokan Hilir Regency. To obtain the data needed, the writer uses descriptive statistical analysis techniques and inferential analysis. Based on the results of this study, it can be seen that 1) There is a positive contribution between the supervision of the principal on the performance of teachers in SD Negeri Bangko District, Rokan Hilir Regency. This means that the better the supervision of the principal, the better the teacher's performance in carrying out their duties. 2) There is a positive contribution between rewards and teacher performance at the State Elementary School in Bangko District, Rokan Hilir Regency. This means that teacher performance can be improved through the provision of rewards in schools. 3) There is a joint contribution of principal supervision and reward on teacher performance at SD Negeri Bangko District, Rokan Hilir Regency. Principal supervision and rewards significantly determine and contribute on teacher performance